Causes and Five-Year Proportion of New Irreversible Visual Impairment in Jinshan District, Shanghai, from 2009–2018 - Tao Li; Xiaodong Zhou (Journal of Ophthalmology)
Purpose. To describe the age distribution and main causes of new registered irreversible visual impairment (VI) and to compare the five-year proportion of VI in Jinshan district, Shanghai, from 2009 to 2018. Methods. The new irreversible VI data were collected in the registry system from the Disabled Persons’ Federation in Jinshan district from January 1, 2009, to December 31, 2018. Age, gender, and causes of VI were included, and the 5-year proportion of VI was calculated. Results. The peak occurrence of blindness occurred in the 50–59 yrs group in 2009–2013 and in the ≥70 yrs group in 2014–2018. The peak occurrence of low vision occurred in the 40–49 yrs group in 2009–2013 and in the 50–59 yrs group in 2014–2018. Myopic macular degeneration (MMD, 15.5%), diabetic retinopathy (DR, 14.3%), and other optic nerve atrophy (ONA, 14.3%) were the three leading causes of blindness in 2009-2013, whereas MMD (21.3%), age-related macular degeneration (AMD, 19.6%), ONA (14.9%) were the three leading causes of blindness in 2014–2018. MMD (39.2%), DR (9.6%), ONA (8.8%) were the three leading causes of low vision in 2009–2013, whereas MMD (38.7%), AMD (23.3%), ONA (7.4%) were the three leading causes of low vision in 2014–2018. The proportions of blindness and low vision caused by AMD were higher in 2014–2018 than those in 2009–2013 (P=0.034 and P<0.001, respectively). Conclusion. The present study demonstrated an increasing trend in the number of irreversibly visually impaired individuals from 2009 to 2018. More attention should be paid to people with high myopia and old age.